Masked blindsight in normal observers: Measuring subjective and objective responses to two features of each stimulus - Koivisto Mika; Neuvonen Susanna (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
Recent visual masking studies that have measured visual awareness with graded subjective scales have often failed the show any evidence for unconscious visual processing in normal observers in a paradigm similar to that used in studies on blindsight patients. Without any reported awareness of the target, normal observers typically cannot discriminate target's features better than chance. The present study examined processing of color and orientation by measuring graded awareness and forced-choice discriminations for both features in each trial. When no awareness for either feature was reported, discrimination of each feature succeed better than expected by chance, even when the other feature was incorrectly discriminated in the same trial. However, the characteristics of the mask determined whether or not masked blindsight was observed. We conclude that when the processing channels are free from infra-channel interference, unbound or weakly bound features can guide behaviour without any reported awareness in normal observers.